TRANSCRANIAL DIRECT CURRENT STIMULATION AND NEURAL MOBILIZATION IN INDIVIDUALS WITH SCIATICA: RANDOMIZED CONTROLLED TRIAL PROTOCOL - Ferreira, Aryostennes Miquéias da Silva; Medeiros, César; Macedo, Liane de Brito; de Souza, Clécio Gabriel (Revista brasileira de fisioterapia (São Carlos (São Paulo, Brazil)), 2024)
BackgroundLow back pain is the leading global cause of disability and Years of Life lived with Disability. About 10% of these episodes are classified as specific, with an identified cause, and may be related to discopathies with neurological deficits, including low back-related leg pain. With three months of persistent pain, it is classified as chronic. It has been investigated that chronic musculoskeletal pain conditions promote structural and functional changes in the brain. Thus, using tDCS a treat these changes may add effect in reducing pain intensity when associated with standard radiculopathy treatment, such as Neural Mobilization. ObjectivesTo verify if the effects of tDCS add benefit to pain intensity improvement in individuals with chronic lumbosciatalgia when associated with Neural Mobilization techniques. MethodsRandomized, blinded controlled trial with participants with chronic lumbosciatalgia. The outcomes assessed are pain intensity, through the Numerical Pain Scale (NDS), as primary outcome; and as secondary outcomes, functional disability, through the Roland Morris Disability Questionnaire, and neuropathic symptoms, accessed by the Douler Neuropathique Questionaire (DN4) and Pain-Detect Questionaire (PD-Q). Evaluations will occur at the following times: before and after the intervention and at seven, fourteen, and thirty-day follow-up. The intervention consists of the association of tDCS with Neural Mobilization, and the participants will be randomly allocated to two groups: Experimental (Active tDCS and Neural Mobilization) and Control (Sham tDCS and Neural Mobilization). For the Statistical Analysis, the Kolmogorov-Smirnov test will be applied for data distribution and the Levene test to analyze the homogeneity of variance. ANOVA with a mixed design will be conducted for the primary and secondary outcomes. The interaction of time and group and the inter-group and intra-group differences will be analyzed for all variables. The Bonferroni test will be used in post hoc analyses to determine if there are differences between groups at the different intervention times. ResultsThis trial is being conducted in its pilot study phase. ConclusionIt is hypothesized that subjects presenting neuropathic pain, as in sciatica, may benefit from a treatment approach that stimulates adaptive neuroplasticity towards reducing pain intensity and functional disability by stimulating descending inhibitory pathways. ImplicationsSuch an approach proves promising as it shows a new therapeutic horizon for a condition considered difficult to manage clinically.